Analisis Nilai Tambah Agroindustri Pengolahan Kopi Robusta (Studi Kasus: Kelio Coffee Di Desa Bandung Batu Kecamatan Kabawetan Kabupaten Kepahiang) - Idsan, Rakha Satya; Andanu, Odi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
This study analyzes the total cost, revenue, income, and added value in the Kelio Coffee agroindustry in Bandung Batu Village, Kabawetan District, Kepahiang Regency. The method used is a case study, focusing on the Kelio Coffee agroindustry. Respondents were selected by purposive sampling because this agroindustry processes robusta coffee that has received Geographical Indication (IG) Certification. The study results indicate that the Kelio Coffee agroindustry produces several products: ground coffee, premium ground coffee, green beans, premium green beans, and roasted beans. The total cost incurred by this agroindustry is IDR 78,694,982.14, with revenue of IDR 108,921,600 and income of IDR 30,226,617.86. The added value ratio of each product is 80.44% for raw ground coffee, 88.70% for premium ground coffee, 47.21% for raw green beans, 69.48% for premium green beans, and 85.45% for roasted beans.